Clinical Evaluation of Safety and Efficacy of a 670-nm Picosecond Laser for Treatment of Benign Pigmented Lesions in Asians - Kristy E.R. Evangelista (2022)
BACKGROUNDPicosecond lasers are increasingly being investigated in treating pigmentation disorders because they may provide better treatment efficacy and comfort compared with nanosecond lasers.OBJECTIVEThis study aims to evaluate the efficacy and side effect of a novel 670-nm picosecond laser in the removal of benign pigmented lesions (BPLs) in individuals with Fitzpatrick skin types (FST) III and IV.MATERIALS AND METHODSFifteen subjects with solar lentigines and 7 subjects with ABNOMs received a single treatment with a 670-nm picosecond laser. Blinded physicians assessed the pigment clearance using a 5-category grading system scale. All subjects were evaluated at 1 month, 3 month, and 6 month after a single treatment. Adverse events were recorded at every follow-up visit.RESULTSAll subjects with lentigines had complete clearance (95%-100%) of lesions during 3-month follow-up after a single treatment session of 670-nm picosecond laser, whereas 75% of the subjects with ABNOMs noted fair lightning (25%-49%) of lesions. Mild hypopigmentation and hyperpigmentation were observed in 9% and 14% of the subjects, respectively, which resolved within 3 months after the treatment.CONCLUSIONThe novel 670-nm picosecond laser is a safe and effective treatment for BPLs in subjects with FST III and IV with low rates of transient adverse effects.